Buddhism in the Modern World: Relevance, Challenges, and Adaptations (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2026)
This paper explores the relevance of Buddhism in contemporary society, examining the challenges it faces and the adaptations it undergoes in a rapidly changing world. As a spiritual and philosophical tradition, Buddhism has evolved from its origins in India over 2,500 years ago to a global faith with millions of adherents. This paper investigates how Buddhism engages with modern issues such as mental health, social justice, and environmental crises while maintaining its core principles. Additionally, it highlights the challenges posed by commercialization, cultural appropriation, and the fragmentation of traditional practices. Through a combination of qualitative analysis and case studies, this paper aims to provide a comprehensive overview of how Buddhism is both preserving its teachings and transforming in the face of modernity.